A prospective cohort of people who use methamphetamine in Melbourne and non‐metropolitan Victoria, Australia: Baseline characteristics and correlates of methamphetamine dependence. (11th November 2020) - Quinn, Brendan; Ward, Bernadette; Agius, Paul A.; Jenkinson, Rebecca; Hickman, Matthew; Sutton, Keith; Hall, Cristal; McKetin, Rebecca; Farrell, Michael; Cossar, Reece; Dietze, Paul M.
Abstract: Introduction and Aims: Limited research has investigated methamphetamine use and related harms in rural and regional Australia. We investigated whether people who used methamphetamine in non‐metropolitan Victoria differed in their sociodemographics and were more likely to be methamphetamine‐dependent than those recruited in Melbourne. Design and Methods: We used baseline data from an ongoing prospective cohort study, 'VMAX'. Participants were recruited from Melbourne and three non‐metropolitan Victorian regions. Sequential multivariable logistic regression of nested models assessed unadjusted and adjusted associations between residential locations and methamphetamine dependence. Results: The sample mostly (77%) comprised people who used methamphetamine via non‐injecting means ( N  = 744). Thirty‐nine percent were female. Melbourne‐based participants were less likely than non‐metropolitan participants to identify as Aboriginal and Torres Strait Islander, be heterosexual, have children and be unemployed. More frequent methamphetamine use (adjusted odds ratio 1.22, 95% confidence interval 1.12–1.34) and using crystal methamphetamine versus 'speed' powder (adjusted odds ratio 2.38, 95% confidence interval 1.26–3.64) were independently ( P  < 0.05) associated with being classified as methamphetamine‐dependent. A significantly higher percentage of participants in every non‐metropolitan region were classified as methamphetamine‐dependent vs. those in Melbourne, but this relationship was attenuated when adjusting for methamphetamine use frequency and primary form used. Despite 65% of participants being classified as methamphetamine‐dependent, less than half had recently (past year) accessed any professional support for methamphetamine, with minimal variation by recruitment location. Discussions and Conclusions: VMAX participants in non‐metropolitan Victoria were more likely to be methamphetamine‐dependent than those living in Melbourne. Unmet need for professional support appears to exist among people using methamphetamine across the state, regardless of geographical location.